Periodontal treatment of patients with hereditary hemorrhagic telangiectasia - de Paiva Gonçalves, Vinícius [UNESP] (2022)
Hereditary hemorrhagic telangiectasia (HHT) is a rare condition in which fragile vascular walls lead to increased risks of bleeding, cerebral abscesses, arteriovenous malformations, anemia, and thrombosis. To date, no protocol has been established for optimizing the clinical outcomes of periodontal treatment in patients with this condition. The aim of this case report is to describe a safe clinical approach to periodontal treatment in a patient with HHT. A 39-year-old woman had a history of multiple macules on the oral mucosa, and a diagnosis of HHT was made based on the Curaçao diagnostic criteria (epistaxis, telangiectases, visceral lesions, and family history). Evaluation of the patient’s periodontal clinical parameters and radiographs led to a diagnosis of generalized periodontitis, stage IV, grade C. The patient underwent nonsurgical periodontal therapy consisting of supragingival and subgingival scaling and root planing under a careful and specific protocol that included antibiotic prophylaxis before each session. Two months after therapy, the periodontal reevaluation showed improvement in the clinical parameters at most sites. Sites with remaining periodontal pockets were re-treated according to the same protocol, including the antibiotic prophylaxis. The patient was enrolled in a periodontal maintenance program, and her HHT was routinely monitored by her physician. Periodontal treatment may promote secondary complications in patients with HHT if appropriate systemic care is not provided, and the periodontal treatment plan should be designed individually for each patient. Establishing the correct HHT diagnosis and coordinating care with the patient’s physician are essential to safe, effective treatment.